Patients with Rapidly (Crescentic) Progressive Glomerulonephritis after Strepococcal Infection: A Case Report - Hengki Wijaya, Nunuk Mardiana (South Eastern European Journal of Public Health, 2025)
Rapidly Progressive Glomerulonephritis (RPGN) is a rare and prevalent condition worldwide, with an incidence of approximately 7 cases per 1 million people in the United States each year. It is the most common cause of kidney injury at a young age in the Middle East, Africa, Australia, and worldwide. The cause of death in RPGN is usually pulmonary involvement. The approach to diagnosis and therapy of RPGN is challenging for clinicians. A 24-year-old woman presented with symptoms such as shortness of breath, edema, subconjunctival hemorrhage, and red and foamy urine. The patient had a history of fever and swallowing pain. Initial therapy included ampicillin sulbactam, metronidazole, furosemide, candesartan, and nifedipine GITS. On day 8, the patient experienced worsening shortness of breath and anuria. Hemodialysis and methylprednisolone pulse therapy were initiated, and the patient improved clinically. Outpatient therapy included methylprednisolone, azathioprine, nifedipine GITS, ramipril, and bisoprolol. The patient's kidney biopsy results showed a 61% glomerular crescentic condition with negative IF IgG, IgA, IgM, C1q, and C. Untreated RPGN can lead to rapid loss of renal function.